ANALYSIS OF METASTASIS-FREE SURVIVAL IN PATIENTS WITH SMALL CHOROID MELANOMA DEPENDING ON THE TYPE OF PRIMARY TUMOR TREATMENT - L. V. Naumenko; S. A. Krasny; K. P. Zhylayeva; A. A. Evmenenko; I. Y. Zherko (Сибирский онкологический журнал, 2021)
Background. There is no unified approach to the management of patients with small choroid melanoma (CM) (thickness up to 3 mm, base diameter up to 10 mm). The study of the development of metastases in these patients is of great significance for choosing an appropriate treatment method.Purpose: to assess the incidence of metastatic disease in patients with small CM, who were treated with transpupillary thermotherapy (TTT), photodynamic therapy (PDT), and brachytherapy (BT).Material and Methods. The retrospective study included 149 patients with CM, who were treated at the National Cancer Center of Belarus from 2005 to 2018. All patients had tumors less than 10 mm in diameter, less than 3 mm in thickness, and had no signs of systemic progression before starting therapy. All tumors corresponded to stage T1N0M0 (American Joint Committee on Cancer (AJCC)). 44 patients were treated with PDT, 47 with TTT, and 58 with BT.Results. The median follow-up time was 154 months (12 years) in patients treated with brachytherapy, 128 months (10 years) in patients treated with TTT and 72 months (6 years) in patients treated with PDT. During the follow-up period, metastases were observed in 1 (2.3 %) patient after PDT and in 5 (10.6 %) patients after TTT. In patients treated with BT, systemic progression was not recorded during the follow-up period. All cases of metastatic disease were associated with local recurrence or continued growth of CM.Discussion. The 5-year metastasis-free survival after TTT was worse than after PDT (82 ± 8.0 % and 94 ± 6.0 %, respectively, p<0.0001). However, in some cases, preference can be given to laser treatment methods, allowing the patients to avoid post-radiation retinopathies. The lack of local control of the tumor can be considered a surrogate marker for the development of metastatic disease. Conclusion. The highest metastasis-free rates were observed after brachytherapy. Positron emission tomography is recommended for early detection of systemic progression of the disease. Key words: choroid melanoma, uveal melanoma, transpupillary thermotherapy, photodynamic therapy, brachytherapy, metastatic-free survival, organ-preserving treatment.>˂0.0001). However, in some cases, preference can be given to laser treatment methods, allowing the patients to avoid post-radiation retinopathies. The lack of local control of the tumor can be considered a surrogate marker for the development of metastatic disease.Conclusion. The highest metastasis-free rates were observed after brachytherapy. Positron emission tomography is recommended for early detection of systemic progression of the disease.